Green Economy and Occupational Health and Safety: Potential Impacts and Preventive Policies - Valenti, Antonio (International Journal of Occupational and Environmental Medicine, 2018)
This perspective connects green economy transitions with occupational health and safety. It outlines potential hazards, workforce training needs, and prevention policies to ensure safe, sustainable jobs.
Keywords: Green Economy; Occupational Health And Safety; Hazards; Workforce Training; Prevention Policies